A prevalência de fatores de risco cardíaco isquêmico em bombeiros militares - Pereira, Cleber Valinodo (2016)
Cardiovascular diseases have been considered a major problem for the health of workers in the Military Police, identified as responsible for a large spacings index and often leading to death, they are causing high demands and high costs in hospital care. Thus, it was intended in this study to identify the prevalence of ischemic cardiac risk factors in all the fire of the 5th Regional Fire Command in Serra gaúcha in 2015. The study was transversal. Data were obtained as follows: structured interview, anthropometric, biochemical, hemodynamic, electrocardiographic, test application of physical fitness and Framingham score. The group consisted of 206 firefighters serving on the 5th CRB, predominantly male, with an average of 34 years old. In the anthropometric variables the study showed 46 firefighters (22.3%) out of the reference standards as the total body mass. All biochemical variables fire study showed 24 (11.7%) out of the reference patterns for total cholesterol, and HDL appears altered in 15 (93.75%) in females and LDL appears altered in 29 (14 02%) overall. The hemodynamic variables all participants were evaluated and the study showed 100 firefighters (48.6%) with high blood pressure. In electrocardiographic variables, physical activity level, double product and Framingham score all participants were evaluated and the study showed 76% of firefighters within the benchmarks. In the variables was observed a significant association between total body mass (p = 0.01), waist circumference (p = 0.01), total cholesterol (p = 0.05), LDL (p = 0.01) HDL (p = 0.05) and blood pressure (p = 0.01) with score Framingham.Em synthesis in the assessed group, were identified as prevalent the following risk factors: obesity, high blood pressure and dyslipidemia.